Early-Life Exclusive Breastfeeding History and Its Association with Primary Enuresis in Preschool Children - Pharahita, Syifa Pandya; Hardianto, Gatut; Ningrum, Astika Gita (Rifa'Institute, 2026)
Introduction: Primary enuresis is a common developmental condition in preschool children and may negatively affect psychosocial well-being and family dynamics. Bladder control acquisition depends on neurological maturation, which can be influenced by early-life nutrition. Exclusive breastfeeding provides essential nutrients and bioactive components that support neurodevelopment. Objective: To analyze the association between early-life exclusive breastfeeding history and primary enuresis among preschool children. Methods: An analytic observational cross-sectional study was conducted in the working area of Lengkong Primary Healthcare Center, Nganjuk, Indonesia. A total of 228 children aged 3–6 years were included. Data were obtained using structured questionnaires completed by parents or caregivers. Associations were examined using the Chi-square test and binary logistic regression. Result and Discussion The overall prevalence of primary enuresis was 43.0% and was higher among younger preschool children. Primary enuresis occurred more frequently among children without a history of exclusive breastfeeding than among those with exclusive breastfeeding (p < 0.001). In multivariable analysis adjusting for child age, sex, family history of enuresis, toilet training and drinking habits, sleep pattern, and autonomic-related complaints, breastfeeding history remained statistically associated with primary enuresis. Conclusions: Early-life exclusive breastfeeding history is independently associated with a lower occurrence of primary enuresis among preschool children